Association of alcohol using measures with screening tests and biochemical markers - Şengül, Cem; Balcı Şengül, Ceyhan; Okay, Tuncer; Dilbaz, Nesrin (Journal of Dependence, 2009)
Objective: Screening tests and biochemical markers were useful items in the diagnosis of alcohol using disorders. Relationship of these markers and screening tests with alcohol measures were mentioned in only few studies. We aimed to investigate association between alcohol measures and alcohol using disorders identity test (AUDIT) and biochemical marker levels. Method: 48 male patients whom were diagnosed as alcohol addiction according to DSM-IV criteria were admitted to our study. Alcohol measures like years of alcohol consumption, average standard drink, epileptic seizure and delirium history were wrote down and the association of these parameters with AUDIT and biochemical markers like CDT, GGT and MCV were investigated. Data was evaluated with SPSS 13.0 program. Results: Both CDT level and AUDIT scores were associated with average standard drink. There was an also association between CDT and years of alcohol consumption. There was statistically significant difference between CDT levels of patients with and without a history of epileptic seizure. No association between addiction parameters and GGT and MCV levels were detected. Conclusions: CDT was superior to other markers and AUDIT in our setting. Previous studies were supporting our findings generally. Repeating of these findings with comprehensive studies would elucidate clinical practice.